Mengidentifikasi Kisah-Kisah Dalam Al-Qur’an dan Menemukan Hikmah di Dalamnya Menurut Ulama Manna Al Qattan - M. Habib Ismail Ramadhan; Muhammad Alfiansyah; Dedi Masri; Shah Umar Hazrian (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In uncovering the insights contained in the stories of the Koran, the researcher conducted a top-down examination of the background of the verses of the Koran, focusing on the structure of the story, the personality of the characters, and the ethical messages contained therein. They also use Islamic learning standards, such as tawhid (belief in one God), profound qualities (ethical qualities), and morals, as reasons for finding shrewdness suggested. This exploration makes a significant commitment to increasing our understanding of possible interpretations of the Qur'an and understanding how researchers differentiate the stories in it and trace the asceticism in it. By knowing these tips, Muslims can apply them in their regular routines and determine the otherworldly and moral advantages of studying the Koran.